Silver telluride nanoparticles as biocompatible and enhanced contrast agents for X-ray imaging: an in vivo breast cancer screening study - Nieves, Lenitza M. (Nanoscale, 2021)
Silver sulfide nanoparticles (Ag(2)S NPs) have gained considerable interest in the biomedical field due to their photothermal ablation enhancement, near-infrared fluorescence properties, low toxicity levels, and multi-imaging capabilities. Silver telluride nanoparticles (Ag(2)Te NPs) have similar properties to Ag(2)S NPs, should also be stable due to an extremely low solubility product and should generate greater X-ray contrast since tellurium is significantly more attenuating than sulfur at diagnostic X-ray energies. Despite these attractive properties, Ag(2)Te NPs have only been studied in vivo once and at a low dose (2 mg Ag per kg). Herein, for the first time, Ag(2)Te NPs’ properties and their application in the biomedical field were studied in vivo in the setting requiring the highest nanoparticle doses of all biomedical applications, i.e. X-ray imaging. Ag(2)Te NPs were shown to be stable, biocompatible (no acute toxicity observed in the cell lines studied or in vivo), and generated higher contrast, compared to controls, in the two X-ray imaging techniques studied: computed tomography (CT) and dual-energy mammography (DEM). In summary, this is the first study where Ag(2)Te NPs were explored in vivo at a high dose. Our findings suggest that Ag(2)Te NPs provide strong X-ray contrast while exhibiting excellent biocompatibility. These results highlight the potential use of Ag(2)Te NPs in the biomedical field and as X-ray contrast agents for breast cancer screening.